PENGARUH PENDEKATAN PROBLEM POSING UNTUK MENINGKATKAN HASIL BELAJAR SISWA SMP KELAS VIII - Wulan Yuni Sawitri; Riana Riana; Luvy Sylviana Zhanty (Jurnal Karya Pendidikan Matematika, 2020)
The teacher-centered learning process causes students to not be able to build their own knowledge, so students easily forget a learning result in low learning outcomes. The learning process that involves students playing an active role is needed at this time one of which uses the problem posing approach. This study aims to see the effect of the problem posing approach to improve learning outcomes of VIII grade junior high school students. This research uses quasi experiment. The sample selection is done randomly by paying attention to students' heterogeneous academic ability, based on the grades of mathematics subjects. The results showed a significant difference in the average value of student learning outcomes from conventional classes and problem posing classes. So the problem posing approach can be used to improve student learning outcomes.